2020
DOI: 10.2147/ijn.s233789
|View full text |Cite
|
Sign up to set email alerts
|

<p>Recent Developments in the Facile Bio-Synthesis of Gold Nanoparticles (AuNPs) and Their Biomedical Applications</p>

Abstract: Gold nanoparticles (AuNPs) are extensively studied nanoparticles (NPs) and are known to have profound applications in medicine. There are various methods to synthesize AuNPs which are generally categorized into two main types: chemical and physical synthesis. Continuous efforts have been devoted to search for other more environmental-friendly and economical large-scale methods, such as environmentally friendly biological methods known as green synthesis. Green synthesis is especially important to minimize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
168
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(172 citation statements)
references
References 137 publications
3
168
0
1
Order By: Relevance
“…Thus, the results show that Hsp-AuNPs were able to particularly stimulate the delivery of hesperidin to cancer cells 29 . Previous studies also reported rapid release of chemotherapeutic drug loaded on AuNPs in acidic conditions when compared to neutral conditions 30,31 .…”
Section: Synthesis Of Hsp-aunpsmentioning
confidence: 86%
“…Thus, the results show that Hsp-AuNPs were able to particularly stimulate the delivery of hesperidin to cancer cells 29 . Previous studies also reported rapid release of chemotherapeutic drug loaded on AuNPs in acidic conditions when compared to neutral conditions 30,31 .…”
Section: Synthesis Of Hsp-aunpsmentioning
confidence: 86%
“…A green synthesis approach was used for the preparation of EGCG-loaded GNPs where HAuCl 4 was reduced in aqueous solution using EGCG. This approach is eco-friendly, clean, simple, efficient, and avoids the use of hazardous man-made chemicals [25,32]. EGCG has eight orthophenolic hydroxyl groups, which form complexes with Au 3+ ions and facilitate their reduction to gold ions to form EGCG-capped GNPs [25].…”
Section: Preparation Of Egcg-gnpsmentioning
confidence: 99%
“…The GNPs were synthesized using a "green" methodology which ensures effective use of EGCG where it serves a triple purpose; the main therapeutic agent, a reducing agent for gold chloride and a stabilizing agent for the formed GNPs. Further, this methodology avoids the use of man-made chemicals as reducing agents, which is environment-friendly, easy to scale up, and limits potentially toxic byproducts produced during GNPs synthesis [32]. EGCG-loaded GNPs were characterized for particle size and morphology, polydispersity index, drug encapsulation efficiency and drug loading capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Several physical, chemical, and biological methods for the synthesis and assembly of Au‐NPs have already been reported. Among these methods, the biological method, also called green or eco‐friendly synthesis, is eco‐benign, clean, less toxic, and more cost‐effective compared with other synthesis methods (Khan, Ullah, Khan, Mashwani, & Nadhman, 2019; Lee et al, 2020; Lopes, Alves, Pereira, Granjeiro, & Leite, 2019; Siddiqi & Husen, 2017). Previous studies have reported on the biological synthesis of Au‐NPs using microorganisms (bacteria, fungi, and yeasts; Narayanan & Sakthivel, 2010; Pei et al, 2017; Tripathi, Shrivastav, & Shrivastav, 2018) and natural plants ( Salix alba leaves, Sambucus nigra fruit extract, Mentha piperita leaf extracts, flower petals of Moringa oleifera , root extracts of Glycyrrhiza uralensis , Garcinia mangostana fruit peel, Panax ginseng fresh leaves, Magnolia officinalis , and Rabdosia rubescens , etc.…”
Section: Introductionmentioning
confidence: 99%